As narrativasimagens dos estudantes sobre os usos que fazem do facebook e a tessitura de relações de amizade com os currículos-entre- redes em uma escola de ensino médio - Lucena, Wellington Machado (2016)
The text presents the study of the quotidian life of a secondary school of the state of Espirito Santo State, located in the municipality of Vila Velha/ES.The research aims to put in discussion the plans of intensity travelled with the traditions of the social network by students practitioners of quotidian life of a public high school, and how those plans of intensity the friendly relations produce the curricula-among-networks in these tissues, quotidian.The research proposal is justified by the interest of students through the use of social networks that maximize the use of the curriculum by creating other opportunities for interaction and communication.Part of the discussion of the connected society has been discussed in various means getting featured on the wheels of academic conversations, in congresses and scientific meetings that are interested in thinking about education and the teaching practice in this social context. The methodological option made in the production of text is especially for the interest in retiring from the linearity of the cartesian traditional models of research, which in this way it is possible to go beyond the collection of data, and proceed to the data production, looking, reading, listening, feeling, smelling, touching, tasting, arguing…. In this sense, from the search with the search routines to problematize the narrativesimages of students, which uses have been made of these social networks in quotidian life of schools by subject practitioners, especially students, and as such uses differentiated potentiate the relations of friendship produced/created/lived in the curriculum-between-networks. Organized into plateaus, the text refers to the structure of Facebook pages, so we are calling for better understanding of the plateaupage. The plateaus were designed in such a way that the reading of the text can be performed independently of the order, as well as on the social network there is an order of access, but an interest in accessing certain content, without beginning or end. It stresses that the curriculum-between-networks, as a possibility of curriculum created from the relations of friendship and of the meetings constituted in social networks, can be perceived in the practices which constitute the quotidian life of the schools when the uses that are made of social networks across the demands of classroom room, either with the uses that make the contents of school, work, artistic presentations is with other movements. What was perceived in the way to school for the production of research, is that the social interactions established in social networks guide the school activities promoted by the students and teachers when the subjects discussed in social networks will also be the main themes of the school activities performed